Literatures Review Nanotechnology as a novel strategy for prevention, diagnosis, control, and treatment tools against COVID19 - Alwan Al Qushawi; Sajjad Mohsin Irayyif; Reham Najem Abdulridha; Jiheel. M.J (Genius Journals, 2024)
On January 30, 2020, the World Health Organization's (WHO) Emergency Committee declared a worldwide health emergency. Now world health faces a risk for the novel serious respiratory disease known globally as the COVID-19 pandemic called Coronavirus 2 (SARS-CoV-2). The infection responsible for COVID-19 is thought to have originated in the Wuhan Province of China. This virus has raised concerns around the world due to its rapid dissemination, great mobility, and high fatality rate. Unfortunately, there isn't even an active and specific antiviral medication or vaccine for COVID-19. Regretfully, while the majority of currently available treatments aid these medications, infections are not completely eradicated. These medications lessen side effects and problems. Many health issues and infections that are expected to pose a serious threat to human health can be addressed by nanomedicine and nanotechnology. Nanomedicine can be detected in the case of viruses that cause respiratory illnesses. A few studies on the application of nanomaterials in the detection of anti-infections and treatment of certain coronavirus strains have been carried out. Based on earlier findings from numerous different coronavirus types, vaccinations associated to nanotechnology have demonstrated a more strong immune response. To imagine the possibility of using nanomaterials in the delivery of a highly effective COVID-19 approach, a review of studies on the potential use of nanoparticles for prevention, identification, monitoring, and care aims was undertaken. Even though there isn't enough research on novel and dramatic therapeutic nanotechnology methods to COVID-19, the next paper review can examine them in order to develop SARS-CoV-2 nanomedicine that is both efficient and successful.
Keywords: COVID-19; SARS-CoV-2